Development Residential Property for B40: A Proposed Collaboration Framework Between Islamic Bank, Waqf, and Zakat Institutions - Muhammad Rawi Ravi, Muhammad Imran; Redzuan, Nur Harena (UUM Press, 2022)
Economic conditions in the aftermath of the Covid-19 pandemic create an uncertain environment for all levels of the community, resulting in anxiety for everyone. The majority of the B40 group has difficulty obtaining credit from banks due to a lack of credit history and collateral. The B40 group is among the affected in obtaining financing from any financial institution. It makes it more difficult for them to buy a house and obtain financial assistance from financial institutions. As a result, they are unable to own their house and resulting to rent a house for their whole lifetime. It is worsened for this vulnerable group to pay the monthly house rental due to unstable income. Eventually, the house rentals arrears accumulate over several months, which could cause them to be evicted from the rented house. Therefore, the study aims to discuss the issues and challenges for the B40 group in Malaysia to own a home and explore a feasible solution for affordable housing on waqf land, while also proposing a framework for the development of residential property on waqf land in Malaysia by a collaboration between related stakeholders. This study incorporated primary data by conducting an in-depth analysis of the interview sessions from the targeted respondents. A series of interview questions are posed about the issues and challenges of B40 in owning a house, and the proposed framework to elicit feedback from industry practitioners regarding its viability and perspectives. The study discovers that the Islamic bank could play a significant role by acting as a collection agent from the public as a source of funding and channeling the fund to the waqf organizations or directly to this project. The study also proposes solar energy utilization within the framework which may help to mitigate greenhouse gas emissions while also addressing the United Nations' sustainable development agenda. This research offers the originality of the finding for the proposed collaboration framework between the Islamic banks, waqf, and zakat institutions in developing the residential property for the B40 group. This research contributes to improving the B40 group’s standard of living by providing a more comfortable house to live in for a long-term period, while also sparking an idea for other researchers to further improve the framework for other environmental aspects.